Seed Dispersal by Forest Chimpanzees in Uganda - Wrangham, R. W.; Chapman, C.A.; Chapman, L. J. (Journal of Tropical Ecology, 1994)
The role of chimpanzees (Pan troglodytes) as seed dispersers in the Kibale Forest Reserve of western Uganda was assessed by analysing 1849 dung samples from two chimpanzee communities and by conducting germination trials on dispersed and non-dispersed seeds. Of the chimpanzee dung samples, 98.5% contained seeds, and fig seeds were the most common. The number of large seeds (>2 mm) per dung sample was often high, even for species with a relatively large seed. For example, Mimusops bagshawei has a 15-mm diameter seed and had an average of 26.5 seeds per sample. In addition, many seed species were found in the dung repeatedly over several months. Germination trials demonstrated that the species of seed commonly collected from dung were viable. Comparisons of both the rate and success of germination of chimpanzee-dispersed seeds with seeds collected directly from the parent trees, showed that gut passage increased the speed and probability of germination. The number of large seeds dispersed by the chimpanzee population was estimated at 369 large seeds km-1 day-1. We suggest that in Kibale, chimpanzees may play a more significant role in primary seed dispersal than implied by their low numbers and biomass.